(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the state policy towards youth in our country and the regulatory documents adopted to bring it to a new level, the main tasks and achievements within the framework of these tasks defined in them. The most important achievements and modernization of educational processes, training of specialists in accordance with world requirements, reform and improvement of the education system, and introduction of innovative technologies are revealed in detail.